Hail netting: an economically competitive IPM alternative to insecticides for Midwest apple production - DiGiacomo, Gigi; Nelson, Sally G. A.; Jacobson, John; Klodd, Annie; Hutchison, William D. (Frontiers in Insect Science, 2023)
The economic costs and benefits of hail netting as a sustainable pest management strategy were explored in this study for Midwest U.S. apple (Malus x domestica). Apple orchards are highly managed agricultural ecosystems where growers typically rely on insecticides to minimize the risk of pest-related fruit losses. Apple growers practicing integrated pest management require cost-effective alternatives to conventional insecticides for control of major pests such as codling moth (Cydia pomonella L.) and apple maggot (Rhagoletis pomonella Walsh). Exclusion netting has been shown to effectively control multiple insect pest species, limit fruit damage and reduce the use of insecticides while also conferring consumer and environmental benefits. In this study, partial budgeting was applied to explore the financial efficacy of using a hail netting (DrapeNet®) system on two Minnesota apple orchards. The cost of the hail netting was compared to a common Midwest insecticide spray regimen for apples using yield and quality data. Despite substantial investment costs, the PB analysis indicated that the netting system was an economically competitive alternative to a conventional pest management system with 5-7 insecticide applications. The economic results were robust across a range of apple prices and yields suggesting that Minnesota apple growers can benefit economically from the application of hail netting for sustainable pest management.